Hudson's Bay Company blockhouse at Fort Colville, Colville Washington - Palmer, Frank, 1864-1920
Small wooden blockhouse Caption on mount: Blockhouse at the old fort of the Hudson Bay Trading Co., near Colville, Stevens Co., WA. Established in 1854 for protection against the Indians Caption on mount of 2nd print: Blockhouse built by the Hudson Bay Trading Co. in 1856, Stevens Co., WA.